Simulations of the flipping images and microparameters of molecular orientations in liquids according to the molecule string model - 王丽娜 赵兴宇 张丽丽 黄以能 (Chinese physics B, 2012)
The relaxation dynamics of liquids is one of the fundamental problems in liquid physics, and it is also one of the key issues to understand the glass transition mechanism. It will undoubtedly provide enlightenment on understanding and calculating the relaxation dynamics if the molecular orientation flipping images and relevant microparameters of liquids are studied. In this paper, we first give five microparameters to describe the individual molecular string （MS） relaxation based on the dynamical Hamiltonian of the MS model, and then simulate the images of individual MS ensemble, and at the same time calculate the parameters of the equilibrium state. The results show that the main molecular orientation flipping image in liquids （including supercooled liquid） is similar to the random walk. In addition, two pairs of the parameters are equal, and one can be ignored compared with the other. This conclusion will effectively reduce the difficulties in calculating the individual MS relaxation based on the single-molecule orientation flipping rate of the general Glauber type, and the computer simulation time of interaction MS relaxation. Moreover, the conclusion is of reference significance for solving and simulating the multi-state MS model.